2020
DOI: 10.3390/ijerph17072468
|View full text |Cite
|
Sign up to set email alerts
|

Association between Weight Status and Physical Fitness in Chinese Mainland Children and Adolescents: A Cross-Sectional Study

Abstract: Background: The increasing prevalence of obesity among children and adolescents is a major public health challenge worldwide. This study examined the relationship between physical fitness and BMI spanning the range from underweight to obese among Chinese mainland children and adolescents. Methods: Participants were 22,681 children and adolescents (11,300 boys and 11,381 girls) aged 10–18 years from the Chinese mainland. Weight status was classified as underweight, normal weight, overweight, and obese using WHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 21 publications
4
32
1
Order By: Relevance
“…Overweight and obese adolescents also showed poorer SLJ compared to their normal-weight peers. Previous studies reported similar results, showing that a higher bodyweight could be a barrier in fitness tests where quick position changes are required since bodyweight increased the exerted forces during knee extension [50,51]. Moreover, a significantly greater performance in SA was found in normal-weight adolescents compared to overweight and obese adolescents (p = 0.002).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Overweight and obese adolescents also showed poorer SLJ compared to their normal-weight peers. Previous studies reported similar results, showing that a higher bodyweight could be a barrier in fitness tests where quick position changes are required since bodyweight increased the exerted forces during knee extension [50,51]. Moreover, a significantly greater performance in SA was found in normal-weight adolescents compared to overweight and obese adolescents (p = 0.002).…”
Section: Discussionsupporting
confidence: 63%
“…However, opposite results were reported for explosive or dynamic tests, where normal-weight individuals have a greater performance [33,50]. The higher strength levels may be explained by a higher amount of FFM, since underweight adolescents present a lower FFM than obese youths in absolute terms, as has been reported by previous studies [51,53,54].…”
Section: Discussionmentioning
confidence: 74%
“…Similar results were also recently announced in a research conducted by He et al (2019), in which he claims that the body weight increase has a negative association with strength of lifting the body. Regarding BMI index, it was found to be in a very weak negative correlation with strength and endurance of the upper body muscle groups and flexibility, as described in the study of Hu et al (2020).…”
Section: Discussionmentioning
confidence: 72%
“…Results confirm previous studies highlighting that overweight and obese children and adolescents show lower motor performances than normal weight peers (Grao-Cruces et al, 2018;Kwieciński et al, 2018;Abdelkarim et al, 2019) in all tests except in the medicine ball throw test (MBT). Xu et al (2020) evidenced better performances in lower limb strength, flexibility, agility and cardiorespiratory fitness, in normal weight adolescents than the obese peers.…”
Section: Discussionmentioning
confidence: 84%